1989
DOI: 10.1007/bf02096465
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal vascular network of the first web space

Abstract: Thirty dissections were performed on adult non embalmed cadavers, after vascular injection with MICROFIL or Methylene blue. In contrast to the classical descriptions of a single dorsal metacarpal artery, this study shows the existence of a vascular network with 1 or 2 vessels running over or under the deep aponeurosis. Direct cutaneous arteries provide blood supply to the kite flap when the only dorsal metacarpal vessel of the first web space is in a deep situation. The main source of blood supply to the kite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, a Quaba pattern fourth dorsal metacarpal flap is always possible, although 35% of the flaps are actually based on perforators arising from the palmar metacarpal artery. Although there are detailed anatomical studies of the first and second dorsal metacarpal artery flaps (Dautel et al, 1989;Dautel and Merle, 1991;Earley, 1986;Earley and Milner, 1987;Sherif, 1994), there is a paucity of literature regarding the anatomy of the third to fifth dorsal metacarpal arterial flaps. Arria and Gilbert (1992) examined the first to fourth dorsal metacarpal arteries in 30 cadaveric hands and observed that the fourth dorsal metacarpal artery had a connection to the palmar system in 67% of the hands dissected.…”
Section: Discussionmentioning
confidence: 99%
“…However, a Quaba pattern fourth dorsal metacarpal flap is always possible, although 35% of the flaps are actually based on perforators arising from the palmar metacarpal artery. Although there are detailed anatomical studies of the first and second dorsal metacarpal artery flaps (Dautel et al, 1989;Dautel and Merle, 1991;Earley, 1986;Earley and Milner, 1987;Sherif, 1994), there is a paucity of literature regarding the anatomy of the third to fifth dorsal metacarpal arterial flaps. Arria and Gilbert (1992) examined the first to fourth dorsal metacarpal arteries in 30 cadaveric hands and observed that the fourth dorsal metacarpal artery had a connection to the palmar system in 67% of the hands dissected.…”
Section: Discussionmentioning
confidence: 99%
“…Dautel and colleagues [2] described a more detailed anatomical study and mentioned a superficial cutaneous artery directly arising from the radial artery. This vessel was distinguished from the FDMA because it had a very small diameter and ran in a very superficial plane compared to the FDMA network.…”
Section: Discussionmentioning
confidence: 99%
“…One or two branches of the radial sensory nerve were also dissected with the flap (Figure 1(b)). One has to be extremely careful not to injure any large direct cutaneous artery (Dautel et al, 1989; Sherif, 1994), which may run with the cutaneous nerve, as it may be the dominant supply to the flap instead of the FDMCA. The fascia of the interosseous muscle was then incised at the radial border of the flap and dissection was continued deep to this layer protecting the pedicle.…”
Section: Methodsmentioning
confidence: 99%